PERAN BADAN PERTANAHAN NASIONAL DALAM PEMBERIAN HAK MILIK ATAS BIDANG TANAH DI KOTA SAMARINDA - Aji. Muhammad Ario kusuma Wardana (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT AJI MUHAMMAD ARIO KUSUMA WARDANA, NPM. 13.11.1001.1011.052, THE ROLE OF THE NATIONAL LANDING AGENCY IN PROVIDING THE PROPERTY RIGHTS ON THE LAND SQUARE IN SAMARINDA CITY. Faculty of Law University August 17, 1945 Samarinda East Kalimantan. Legal Writing (Thesis). 2017.            The purpose of this research is to know clearly how the role of National Land Agency in the granting of land ownership rights in the city of Samarinda and also to know the constraints faced by BPN in a process of granting of property rights.             This research is a descriptive type of research and also includes normative and empirical research. The research location is located at the office of the National Land Agency of Samarinda City. The type of data used is primary data sourced from the National Land Agency that is Mr. Warisito, SH directly about the secondary data BPN derived from the library and regulations related to the title of the thesis. Data collection techniques used are by conducting interviews directly and then compared with the rules of the Act. Data analysis used is qualitative analysis by comprehending and compiling data which have been obtained and arranged systematically, then drawn conclusion.              Based on the results of my research, it can be concluded that BPN is very important in taking an active role in the process of granting land ownership rights. Within the property there is also a land registration. The granting of land rights and registration is contained in Regulation of the Head of BPN RI No.2 of 2013 on the delegation of land title authority and land registration activities. BPN also has various obstacles in its implementation. Some legal action due to errors in members of the legalization of property rights, but the BPN has a way of settling such as through mediation.Keywords: BPN, Hak Milik, Kota Samarinda